Prognostic value of the neutrophil-lymphocyte, platelet-lymphocyte and monocyte-lymphocyte ratio in breast cancer patients - Huszno, Joanna (Oncol Lett, 2019)
The aim of the present study was to assess the blood the neutrophil-lymphocyte ratio (NLR), platelet-lymphocyte ratio (PLR) and monocyte-lymphocyte ratio (MLR) as prognostic factors in breast cancer (BC) patients. A retrospective analysis of 436 BC patients who were treated at COI (Gliwice, Poland) between January 2005 and June 2018 was performed. The prognostic value [overall survival (OS)] of the pre-treatment PLR, NLR and MLR was assessed by univariate and multivariate analysis. The 5-year OS was lower in the NLR >2.65 compared with that in the NLR≤2.65 group (82.5 vs. 89.6%; P=0.053), and significantly lower in the subgroup of triple-negative breast cancer (TNBC; 70.3 vs. 89.3%; P=0.034) and in patients whose tumors had an estrogen receptor-negative [ER(−)] status (66.6 vs. 83.6%; P=0.018). The 5-year OS was lower in patients with PLR >190.9 compared with that in the PLR≤190.9 group (78.7 vs. 89.4%; P=0.020). A poor OS rate associated with an elevated PLR was also observed in the subgroups with TNBC (68.2 vs. 88.5%; P=0.032) and with ER(−) status tumors (57.7 vs. 83.6%, P=0.002). An elevated MLR (>0.28) was not associated with OS time (P=0.830). Multivariate analysis revealed that the NLR and PLR were insignificant negative prognostic factors, except for the subgroup of patients with ER(−) tumors, where an elevated NLR [hazard ratio (HR)=2.40; 95% confidence interval (CI): 1.20–4.80; P=0.013] and a higher PLR (HR=2.51; 95%CI: 1.23–5.14; P=0.012) were independent prognostic factors for poor OS together with lymph node metastasis ((HR=5.47; 95%CI: 2.46–12.15; P=0.0001 and HR=4.82; 95% CI: 2.15–10.78; P=0.0001), respectively. The present results revealed that an elevated NLR (>2.65) and PLR (>190.9) are associated with poor OS in BC patients. In the ER(−) subgroup of patients, an elevated NLR and PLR were significant independent prognostic factors. However, the MLR did not affect OS.